Everolimus Is Associated With Less Weight Gain Than Tacrolimus 2 Years After Liver Transplantation: Results of a Randomized Multicenter Study. Issue 12 (December 2017) - Charlton, Michael; Rinella, Mary; Patel, Dharmesh; McCague, Kevin; Heimbach, Julie; Watt, Kymberly
Abstract : Background: Weight gain early after transplant is a risk factor for posttransplant metabolic syndrome (PTMS), cardiovascular events, and renal insufficiency. The impact of mammalian target of rapamycin inhibition on posttransplant weight gain and the development of PTMS components postliver transplantation were examined in a randomized, controlled study. Methods: After a run-in period, patients (N = 719) were randomized at 30 ± 5 days posttransplant in a 1:1:1 ratio to 3 treatment groups: (i) everolimus (EVR) + reduced tacrolimus (TAC) (n = 245); (ii) TAC control (n = 243) or (iii) TAC elimination (n = 231). In this post hoc analysis, weight change at 12 and 24 months was compared between groups. Vital signs, lipids, and laboratory parameters at 12 and 24 months and rates of PTMS were assessed. Results: Mean increase in weight from baseline was higher at month 12 in the TAC control arm (8.15 ± 9.27 kg) than in the EVR + reduced TAC (5.88 ± 12.60 kg, P = 0.056) and the TAC elimination arms (4.76 ± 9.94 kg, P = 0.007). At month 24, the TAC control arm displayed a significantly greater weight increase (9.54 ± 10.21 kg) than either the EVR + reduced TAC (6.69 ± 8.37 kg, P = 0.011) or the TAC elimination groups (6.01 ± 9.98 kg, P = 0.024). Rates of PTMS were similar for the EVR + reduced TAC (71.8%), TAC elimination (70.3%) and TAC control (67.4%) arms ( P = NS). Conclusions: EVR with reduced-exposure TAC attenuated weight gain at 1 and 2 years posttransplant compared with a standard TAC immunosuppression regimen. Rates of PTMS were comparable between EVR-containing and TAC control regimens. Abstract : In this randomized controlled trial, liver recipients on tacrolimus reduced or eliminated immunosuppressions gain less weight at 1 and 2 years. Whereas, the chances of developing posttransplant metabolic syndrome not affected. The role of everolimus in this regard remains unclear.